Investigation of single cart gantry crane system performance using scheduling algorithm - Omar, Mohamad Syarafuddin; Jaafar, Hazriq Izzuan; Ghazali, Rozaimi; Mohamad, Syahrul Hisham; Mohd Annuar, Khalil Azha (Blue Eyes Intelligence Engineering & Sciences Publication Pvt. Ltd., 2015)
This paper investigates the implementation of two types of scheduling algorithm to obtain the best performances of the Single Cart Gantry Crane System (GCS). In this research, Deadline Monotonic Priority Assignment (DMPA) and Earliest Deadline First (EDF) scheduling algorithm are chosen to be implemented. The main ideas of this approach is to find the schedule that more compatible and provide more stable result for the system. The Cart performances will be analyzed in term of Settling Time (Ts) and Overshoot (OS). In this study, a simple PID controller that acts as a basic control structure is used. The application of TRUETIME kernel block also is implemented to be executed in a MATLAB environment. It has been demonstrated that implementation of these two algorithms will help this system to be more stabilized according to appropriate execution time.